Grades and standards for african farmers - (:unkn) unknown (My University, 2024)
This dissertation explores constraints preventing markets for quality emergence in sub-Saharan African (SSA) local agri-value chains. It aims to document new facts about quality recognition and constraints preventing quality remuneration. This thesis is organized in 4 chapters on agricultural production and market functioning in SSA agri-food local value chains. The first chapter develops a theoretical model to investigate the role of relational contracts in quality supply and tests it empirically using first-hand transaction data in Ethiopianwheat markets. The second chapter measures returns to quality in rural agricultural markets using the same data. The third chapter combines a theoretical and field experiment approach with Ethiopianwheat traders to test constraints preventing uptake of third-party certification. The last chapter measures the price effects of a social protection program, the Productive Safety Net Program, on local markets prices in Ethiopia.
Keywords: African Research